Tribological Performance Of Graphene Synthesised From Solid Waste Products As Carbon Sources - Mat Tahir, Noor Ayuma (2020)
Graphene is one of the most recent carbon nanomaterials that have attracted a widespread attention due to its excellent properties. Despite intense research on graphene for various applications has been conducted, the tribological properties as self-lubricants solid in coatings technology remains relatively unexplored. There are many studies showings that graphene can be synthesised from variety of carbon-containing sources including waste and bi-products. However, there are limited studies proposed solid waste product as a carbon source. If the synthesised graphene can be readily used without any treatment, the production cost can be lowered, and a good quality coating may be produced to face the demands and challenges in industries nowadays. The objectives of this study are to characterize the chemical bonding and determine the combustion point of fruit cover plastic waste and oil palm fiber. Then, to determine the optimum parameters to synthesise and investigate its tribological performances including comparing its performance with graphene from other studies. This study focused on fruit cover plastic waste and oil palm fiber as solid source by using chemical vapour deposition method. The chemical bonding characterization were conducted by using FTIR spectroscopy analysis meanwhile the combustion point was determined by using combustion in furnace. Based on the FTIR analysis, fruit cover plastic waste was dominated by C-H bond meanwhile C-O bond was dominating the oil palm fibre. The combustion point for fruit cover plastic waste were much lower (600 °C) compared to oil palm fibre (1000 °C). The optimisation was conducted based on Taguchi L9 arrays and Raman spectroscopy analysis were used as the response. The optimum parameters to synthesise graphene from fruit cover plastic waste source are by using Argon gas, at 1020 °C, for 90 minutes, and Hydrogen gas at 1000 °C, for 30 minutes for oil palm fiber. Both graphene coatings are classified under bi-layered and few-layered graphene and provides promising potentials as friction and wear reduction materials where the coefficient of friction obtained from dry sliding test are less than 0.1 for both coating and relatively low wear rate due to the formation of tribolayer on the counter surface. By comparing the coefficient of friction of the graphene synthesised in this study with others, both graphene coatings present lower coefficient of friction compared to the others.